THE IMPORTANCE OF DIGITAL TECHNOLOGIES AND SIMULATION ON THE TOPIC OF SATURATED DIBASIC ACIDS - Aytoreev, Abdiganiy Isaqbaevich; Sherimmatova, Sarvinoz Rasulovna (SCIENCE and SOCIETY, 2026)
The article discusses the importance of digital technologies and simulation in the topic of saturated dibasic acids. Based on modern pedagogical approaches to teaching organic chemistry, students will have the opportunity to develop new materials that develop organic thinking skills, design experiments, and metrological interpretation of results.